2020
DOI: 10.1007/s12325-020-01391-1
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Cancer—Aggressive Variants and Impact on Management: A Narrative Review

Abstract: Introduction: Aggressive variants of papillary thyroid cancer (PTC) have been described with increasing frequency. These variants include diffuse sclerosing variant, tall cell variant, columnar cell variant, solid variant, and hobnail variant. Methods: We have performed a review of the more aggressive variants of PTC with respect to main characteristics, histological and molecular features, and the consequences that the knowledge of these variants should have in the treatment of the patients. Results: At the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
140
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(146 citation statements)
references
References 79 publications
5
140
0
1
Order By: Relevance
“…The BRAF V600E mutation is the most common genetic alteration in PTC, and it is associated with poor clinical outcomes such as regional recurrence and distant metastasis [ 26 , 27 , 28 ]. The results of the current study are consistent with those of previous studies, which reported that BRAF mutation was detected in 80–100% of TCV-PTC and 33% in CCV-PTC [ 2 , 9 ]. As most (69.4%) of the tissue sample from current study was TCV-PTC, the frequency of BRAF mutation was 89%, which was close to that of TCV-PTC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The BRAF V600E mutation is the most common genetic alteration in PTC, and it is associated with poor clinical outcomes such as regional recurrence and distant metastasis [ 26 , 27 , 28 ]. The results of the current study are consistent with those of previous studies, which reported that BRAF mutation was detected in 80–100% of TCV-PTC and 33% in CCV-PTC [ 2 , 9 ]. As most (69.4%) of the tissue sample from current study was TCV-PTC, the frequency of BRAF mutation was 89%, which was close to that of TCV-PTC.…”
Section: Discussionsupporting
confidence: 93%
“…Despite notable progress in the elucidation of genetic profiles of thyroid cancers, studies investigating the mutational profile of aggressive variant PTC are limited and unclear. The BRAF V600E mutation, which has emerged as a marker of aggressive behavior in thyroid cancer, was observed in 80–100% of TCV, 33% of CCV, and 25.3–57.1% of HV [ 9 , 10 , 11 , 12 , 13 ]. The RAS mutation, which may play an important role in follicular thyroid carcinogenesis, is more frequent and may be more relevant as a prognostic indicator in follicular pattern lesions (FV-PTC, follicular thyroid carcinoma (FTC), and PDTC) than in classical PTC [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The main difference regarding the diffuse involvement of thyroid gland by a PTC concerns the association of diffuse sclerosing variant of PTC with BRAF-like features [72] and the association of diffuse/multinodular FVPTC with RAS-like features. The prognosis of these two variants is associated with usual clinico-pathological factors (Age, Gender, Staging, Lympho-vascular invasiveness) and, as far as we know, there is no evidence for molecular features in risk stratification.…”
Section: Histopathology-aggressive Variants Of Ptcmentioning
confidence: 99%
“…In most instances, the demonstration of rearrangements such as the BRAF fusions may be diagnostically important but the prognostic impact is not clear [76,77]. The same applies to the detection of a number of other rearrangements including RET/PTC1, RET/PTC3, ETV6/ NTRK3 PAX8/PPARγ, ROS1, and ALK [72,76,[78][79][80].…”
Section: Histopathology-aggressive Variants Of Ptcmentioning
confidence: 99%
“…Microscopic extrathyroidal extension is thus considered to be a risk factor for locoregional recurrence but is no longer considered a risk factor for disease-specific mortality; the TNM T3 classification now only includes macroscopic extrathyroidal extension. Aggressive histology, even for small tumors, is considered to be a factor for an intermediate risk of recurrence and includes tall cell, hobnail, columnar cell, and diffuse sclerosing papillary carcinomas [16]. For follicular carcinoma, low-risk tumors include the encapsulated variant, minimally invasive follicular carcinoma, and encapsulated minimally invasive follicular carcinoma with a small number of foci of vascular invasion and without extracapsular vascular invasion [1].…”
Section: What Are Low- Intermediate- and High-risk Cancers?mentioning
confidence: 99%